PENDIDIKAN AKHLAK DAN TOLERANSI SEJAK DINI MELALUI MEDIA HANDBOOK BERBASIS BUDAYA LOKAL MEGAFEST LUPIS RAKSASA - Sari, Fidiyah; Hibana, Hibana (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2024)
Character education in early childhood is crucial in shaping children's personalities and attitudes from an early age. However, many children still struggle to understand character values due to the lack of engaging and culturally relevant learning media. This study aims to develop and evaluate the effectiveness of the Megafest Lupis Raksasa storybook in instilling noble character values and a spirit of tolerance in early childhood. The research employed a qualitative approach with a case study design. The subjects of this study were 15 children aged 4-6 years at TK Batik Wonopringgo, Pekalongan, while the object of the study was a culturally based storybook. Data collection techniques included observation, interviews, and documentation, utilizing an instrument framework to assess children's character aspects. The data were analyzed using thematic analysis techniques to identify patterns in children's character development. The findings indicate that using a culturally based storybook enhances children's understanding of character values such as sharing, cooperation, and respecting differences. This study recommends integrating culturally based media into the early childhood education curriculum and providing training for educators to optimize the use of culturally relevant learning media.